Investigation the Antioxidant Features and Therapeutic Potential of Onion Peel Husk on Elevated Liver Enzymes with Induced Liver Fibrosis in Male Albino Rats - Aslam, Kiran; Qura-tul-ain; Farooq, Aqsa; Saeed, Maham; Mukhtar, Hafiza Nimra; Fatima, Arooj; Habib, Sidra; Azmat, Menahil (Indus Journal of Bioscience Research, 2025)
Liver inflammations and fibrosis can be due to liver injury. In liver fibrosis, inflammations which trigger myofibroblasts in the liver release extracellular matrix proteins that produce fibrous scar. There exist a number of plants which are helpful in regulating the malfunctioning of liver enzymes in liver fibrosis. Onion peel contains quercetin which is effective against the management=nt of malfunctioning liver enzymes. 15 albino male subjects were induced with liver fibrosis using carbon tetrachloride injection to investigate their elevated liver function enzymes when given different doses of red onion peel. The serum level of alanine transaminase and aspartate transaminase enzymes were investigated. While members of treatment groups I (T1) and II (T2) received ROP powder in encapsulated quantities of 150 mg and 300 mg per kilogram of body weight, respectively, for 15 days, members of the control group (T0) received no therapy. Onion peel powder can be useful in treating malfunctioning liver enzymes in caused liver fibrosis, as seen by the significant decrease in liver enzymes seen in treatment groups. All results were taken significantly at p<0.05.